2016
DOI: 10.1002/chem.201504453
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Photodegradation of Naphtho[2,3‐g] quinoxalines and Pyrazino[2,3‐b]phenazines

Abstract: Nitrogen-containing polycyclic aromatic hydrocarbons are very attractive compounds for organic electronics applications. Their low-lying LUMO energies points towards a potential use as n-type semiconductors. Furthermore, they are expected to be more stable under ambient conditions, which is very important for the formation of semiconducting films, where materials with high purity are needed. In this study, the syntheses of naphtho[2,3-g]quinoxalines and pyrazino[2,3-b]phenazines is presented by using reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Alternatively, direct illumination and monitoring has been accomplished within an NMR spectrometer,e ither by installing al ight source inside the instrumento ru sing an optical fiber,w hich typically requires probe modificationo racoaxial glass insert, respectively. [31][32][33][34][35][36][37][38][39][40][41][42][43] The use of light-coupled optical fibers with NMR spectroscopy has distinct advantages from the standpoint of technical simplicity,c ompatibility with aw ide radiation range (UV-IR), and relativelyl ow cost (comparedt op robe modifications). Apart from traditional coaxial capillaryi nserts, "pencil tip" inserts [38,39] and fiber-tipe tching procedures [31,33] have been utilized to pro-As imple, inexpensive, and modularm ethod to directly illuminate NMR samples for in situ analysis of photochemical transformations is reported.T he versatility of this technique is demonstrated by analyzing the light-induced propagating front for small-molecule photoswitchesa nd the kinetics of photocontrolled living radical polymerizations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, direct illumination and monitoring has been accomplished within an NMR spectrometer,e ither by installing al ight source inside the instrumento ru sing an optical fiber,w hich typically requires probe modificationo racoaxial glass insert, respectively. [31][32][33][34][35][36][37][38][39][40][41][42][43] The use of light-coupled optical fibers with NMR spectroscopy has distinct advantages from the standpoint of technical simplicity,c ompatibility with aw ide radiation range (UV-IR), and relativelyl ow cost (comparedt op robe modifications). Apart from traditional coaxial capillaryi nserts, "pencil tip" inserts [38,39] and fiber-tipe tching procedures [31,33] have been utilized to pro-As imple, inexpensive, and modularm ethod to directly illuminate NMR samples for in situ analysis of photochemical transformations is reported.T he versatility of this technique is demonstrated by analyzing the light-induced propagating front for small-molecule photoswitchesa nd the kinetics of photocontrolled living radical polymerizations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, removing aliquots from a reaction can lead to contamination (e.g., oxygen) and continually decreases the volume of the system. Alternatively, direct illumination and monitoring has been accomplished within an NMR spectrometer, either by installing a light source inside the instrument or using an optical fiber, which typically requires probe modification or a coaxial glass insert, respectively . The use of light‐coupled optical fibers with NMR spectroscopy has distinct advantages from the standpoint of technical simplicity, compatibility with a wide radiation range (UV–IR), and relatively low cost (compared to probe modifications).…”
Section: Introductionmentioning
confidence: 99%
“…This is associated with their significantly higher IP values. Detailed studies of the degradation of naphtho[2,3- g ]quinoxalines and pyrazino[2,3- b ]phenazines showed that the degradation starts by oxidation of three rings to their peroxide form and then their further transformation to quinones [ 75 ]. The terminal ring turned out to be the most resistant in this process whereas the degradation process started by oxidation of the ring adjacent to it.…”
Section: Degradation Of Linear Azaacenesmentioning
confidence: 99%
“…[11] Thus, the development of novel imine synthesis protocols is of high interest. [7,12,13] Benzimidazoles [7,14] and quinoxalines [15] are similarly important as well as the developmento fp rotocols for their synthesis. We have recently introduced av ariety of SiCN-metal nanocomposite catalysts [16] and have, very recently,i ntroduced highly active,s elective and reusablec obalt catalysts.…”
mentioning
confidence: 99%
“…The reactionc onditions for 1-iodo-4-nitrobenzene (Table 1; entry 9), had to be modified slightly.O therh ydrogenation-sensitive functional groups,s uch as aldehydes, amides, ketones, and nitriles, could be tolerated too ( Table 1). The temperaturea nd the pressure were slightly increased to ensure full conversion of sterically more demanding substrates (Table 1; entries [15][16][17]. We also investigated (E)-(2-nitrovinyl)benzene but observed am ixture of products since the CÀCd ouble bond was hydrogenated.H eterocyclic nitro compounds work as well as demonstrated for isoquinolin-5-amine (Table 1, entry 18).…”
mentioning
confidence: 99%